PENGARUH LINGKUNGAN KERJA, KEPUASAN KERJA DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KINERJA KARYAWAN (Studi pada Karyawan PT. X) - Efi Nurjanah (Journal of Fundamental Management (JFM), 2023)
This study aims to determine the effect of work environment, job satisfaction and perceived organizational support on the performance of employees of PT. X. The object of this research is the employees of PT. X. The population in this study were 264 employees of PT. X. Based on the Yamane/Slovin formula the sample used in this study was 159 employees. The sampling technique used is probability sampling. The method of collecting data using the survey method, with the research instrument is a questionnaire. The approach used in this research is the Structural Equation Model (SEM) with the SmartPLS analysis tool. The results of this study indicate that the work environment, job satisfaction and perceived organizational support have a positive and significant effect on the performance of PT.X employees.